ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM JAKARTA ISLAMIC INDEX (JII) - Darwis Harahap (Journal Analytica Islamica, 2016)
The development of Islamic Mutual Fund in the form of Islamic investment in the capital market has not been socialized as it relates to the approval of the controversy has not kesyariahan mechanism of transactions in the capital market.One approach in assessing the company's stock price is to assess the company's book that looks at the balance sheet represents a company whose liquidation value or replacement cost of assets now. While some stock analysts formulate the company's stock price based on the stock price changes in the past, which is the main analysis graph or chart.To answer the question (reseach question) is filed, it will be used a number of variables and statistical and econometric analysis as follows: Pricet Ln = β0 + β1 + β2 ln ln SALES BV + β3 + β4 DER Ln Ln Ln EXCHANGE SBI + β5 + β6 Pricet Ln-1 + eResults Movement of sales (sales) significantly positively affect the shares of PT. Aneka Tambang (Persero) Tbk. And PT. Indonesian Satellite Corporation (Persero) (Indosat) Tbk. The book value (book value) of assets of PT. Aneka Tambang (Persero) Tbk. Significant positively affect the price of shares. Indonesian Satellite Corporation (Persero) (Indosat) Tbk. The movement of the debt ratio (debt ratio) PT. Indonesian Satellite Corporation (Persero) (Indosat) Tbk. significantly affect the company's stock price negatively. Movements in interest rates significantly negatively affect the share price on PT. Aneka Tambang. Movements in foreign exchange rates (exchange rate) does not significantly affect the company's stock price of PT. Aneka Tambang (Persero) Tbk. And PT. Indonesian Satellite Corporation (Persero) (Indosat) Tbk. The movement of stock prices significantly pad prior periods positively affects the price of shares. Aneka Tambang (Persero) Tbk. And PT. Indonesian Satellite Corporation (Persero) (Indosat) Tbk.